Vous êtes sur la page 1sur 388

2000

15%

 Z
 R

 R n

a + ib a, b R

3

+ 6i

3

4i

;

1 + i 2 i 2

+

3

+ 6i

3

4i

;

2 + 5i + 2 5i

1 i

1 + i .

a + ib a, b R

+ 2i

5

1 2i

;

1

2

+ i 3

2

3

;

(1 + i) 9

(1 i) 7 .

a + ib

2 π/3

3 π/8

a + ib, a R b R.

z 1 = i,

z 2 = 1 + i,

z 3 = 2 +

2

1

1 + 2i

2 + 5i + 2 5i

1 i

1 + i .

1 i 3

(1 + 2i)(3 i)

1

2i ,

z 1 =

3 + 3i z 2 = 1 3i z 3 = 4 i z 4 = 2 z 5 = e iθ + e 2iθ .

3

( 1+i 3

2

) 2000

2 π/3 3 5π/6

2 π/3 3 5π/6

(3 + 2i)(1 3i)

3+2i

13i

 1 + i(1 + √ 2) 10 + 2 √ 5 + i(1 − √ 5)

tan ϕi

tan ϕ+i ϕ

1 + i

;

1 + i 3

;

3 + i

;

1 + i 3

3 i .

(cos(π/7) + i sin(π/7))( 1i 3 )(1 + i) = 2(cos(5π/84) + i sin(5π/84)),

2

(1 i)(cos(π/5) + i sin(π/5))( 3 i) = 2 2(cos(13π/60) + i sin(13π/60)),

2(cos(π/12)+i sin(π/12))

1+i

= 3i

2

.

u = 6i 2 w = u v

2

v =

1 i

1 + i 3(1 i) 1 + i

2

.

e e iα

e iθ + e 2iθ .

1+i

1i ( 1+i

1i ) 32

Z = (1 + i 3) 2000

z =

n

(1 + i 3) 5 + (1 i 3) 5

(1 + i 3) 5 (1 i 3) 5

1

1+i tan α

z 1 = 1 + i 3 1 + i

;

z 2 = 1 + j

;

z 3 = 1

+ i tan θ

1 i tan θ .

n ( 3+i) n

z ρ θ z

(z + z)(z 2 + z 2 )

(z n + z n ) ρ θ

α β z = e iα + e iβ z = ρe iγ u = α+β

v =

2

αβ

2

n

p

n

C

cos[+ (n p)β].

p=0

(1 + cos φ + i sin φ) (1 + cos φ + i sin φ) n .

1 + e iθ θ ] π, π[

|z| = 1 |1 + z| 1 |1 + z 2 | 1

exp(z) = 3 + 3i

|z| k < 1 1 k |1 + z| 1 + k

1, i, 3 + 4i, 8 6i, 7 + 24i

3 4i 24 10i

sin(π/8)

1+i cos(π/8)

2

cos(π/12) sin(π/12)

az 2 + bz + c = 0 a b c

C

z 2 + z + 1 = 0

;

z 2 (1 + 2i)z + i 1 = 0

;

z 2 3z i = 0

;

z 2 (5 14i)z 2(5i + 12) = 0 ;

z 2 (3 + 4i)z 1 + 5i =

0 ;

z 4 + 10z 2 + 169 = 0

;

z 4 + 2z 2 + 4 = 0.

4z 2 2z + 1 = 0 ;

x 4 30x 2 + 289 = 0.

z C \ {2i}

f(z) = 2z i

z

2i .

z 2 = i, z C.

f (z) = z, z C \ {2i}.

2π

j = e 3 .

 j j 2 1 + j + j 2 = 0

z 3 8i

1 + i 7 + 24i i 5 + 12i 1+i 3

3+i

+ 1 = 0

z 2 + z

z 2 + z 2 = 0

z 2 (5 14i)z 2(5i + 12) = 0

 z 2 + 4z + 5 = 0 z 2 − (3 + 4i)z − 1 + 5i = 0

z 4 (1 i)z 2 i = 0

z 4 + 4z 3 + 6z 2 + 4z 15 = 0

C

 z 2 − (11 − 5i)z + 24 − 27i = 0 z 3 + 3z − 2i = 0

C (E)

z 2 (1 + a) (1 + i) z + 1 + a 2 i = 0,

a

a R z 1 z 2 (E) 2i(1 a) 2

Z 1 Z 2 z 1 z 2 M [Z 1 , Z 2 ] M a

R

α R C z 2 2 cos(α)z + 1 = 0.

z 2n 2 cos(α)z n + 1 = 0, n

P α (z) = z 2n 2 cos(α)z n + 1.

P α

P α (z) = z 2 2 cos α + 1 z 2 2 cos α

n

n + 2π

n

+ 1

z 2 2 cos α

n

+ 2(n 1)π

n

1 cos θ = 2 sin 2 θ ,

2

θ R.

P α (1)

sin 2 2n sin 2 2n + π

α

α

n

sin 2

2n + (n 1)π = sin 2 α

α

n

2

4

n1

.

α ]0, π[ n 2

H n (α) = sin

α

2n +

2n sin

π

2n + 2π

α

n

sin

2n + (n 1)π

α

n

.

α

2 n1 H n (α) = sin(α/2) sin(α/2n) .

H n (α) α 0

n 2

sin π

n sin 2π

n

sin (n 1)π

n

=

n

2 n1 .

n

z C |1 + iz| = |1 iz|.

C 1+iz

1iz n = 1+ia

1ia , a R.

3+i

3i

Z P (Z) = Z 4 1

P (Z) C P (Z) = 0

z

((2z + 1)/(z 1)) 4 = 1

C z 4 = (1 i) / 1 + i 3 .

1

C z 3 = 4 (1 + i)

2 2i 11 + 2i

1+i √ 3
2
2(1+i)

2

sin 12 tan 12 tan 5π C z 24 = 1

cos

π

π

12

π

12

81 81

n N z C

(z 1) 1 + z + z 2 +

+ z n1 = z n 1,

z =

1

1 + z + z 2 +

+ z n1 = z z n 1 1 .

x R exp(ix) 1 = 2i exp ix sin x . n N x R

2

2

Z n = 1 + exp(ix) + exp(2ix) +

+ exp((n 1)ix),

X n

Y n

 = 1 + cos(x) + cos(2x) + + cos((n − 1)x) = sin(x) + sin(2x) + + sin((n − 1)x).

S n = 1 + z + z 2 + ··· + z n

z 3 = 1 1 j j 2

1 + j + j 2 1 + z + z 2 = 0

z n = 1 1, ε,

, ε n1

1 + z + z 2 + ··· + z n1

= 0 p N 1 + ε p + ε 2p + ··· + ε (n1)p

C

z 3

z

z 5 = 1 i

= z 5 = z.¯

5

= 1

2 + 2i

n i 1 + i

 z 2 − z + 1 − i = 0 z 2n − z n + 1 − i = 0

ε n

S = 1 + 2ε + 3ε 2 + · · · + n1 .

C (z + 1) n = (z 1) n

C z n = z n 1

z 6 = 1 + i 3

1 i 3

;

z 4 =

1 i

1 + i 3 .

z 6 + 27 = 0 z C

z 2 z 3 z 1

z 1 z 2 z 3

C

z 6 + (7 i)z 3 8 8i = 0.

Z = z 3 (9 + i) 2

C 27(z 1) 6 + (z + 1) 6 = 0

7 24i

β C β 7 = 1 β

= 1

β

1 + β 2 +

β

2

1 + β 4 +

β

3

1 + β 6 = 2

z

z

z

z

z

5

3

3

5

= 1,

= 2 2

.

C (z 2)/(z 1) = i.

M, A, B z, 1, 2 M

= A

M

= B (z 2)/(z 1)

P C

M (x, y)

x + iy = z,

z M. f : P rg P M z M z =

zi

z+i .

P f

|z | z M

H := {M (x, y) P | y > 0.}?

f H.

P P C

M (x, y)

x + iy = z,

z M. g : P rg P z = 1z

1+z

¯

z + z |z| = 1

M z

=

1 g(M )

1 0 (1, 0) g.

C x 2 xy + y 2 = 0 P

C R

 A = (−3, 2) B = (4, 2) C = (4, −1) D = (−3, −1).

R

A

B

C

D

=

=

=

=

(1, 4)

(2,

(2,

(1, 1).

4)

1)

z

z3

z5

= 1

za

zb

= 1

z

z3

z5

= k k > 0 k

= 1

za

zb

= k

A B C

a b c a+jb+j 2 c = 0 ABC

j j 2 1 j = 1+i 3

ABC BOD OCE D E O ADOE OBC DBA EAC

2

H O M H M M O H H xy = 1

H z 2 z¯ 2 = 4i a M

¯

|z a| 2 = 4aa¯ Z = z a Z

Z + 2a M Z 3 A = 0

u, v C |u + v| 2 + |u v| 2 = 2(|u| 2 + |v| 2 ).

z, z C (z) (z ) = π 2

zz + zz = 0

|z + z | 2 = |z z | 2 = |z| 2 + |z | 2

M z

z(z 1) = z 2 (z 1)

M z

1 z 1 + z 2

s = (1 z)(1 iz)

z s

z s

A α = a + ib

M z |z| 2 = αz¯ + αz.¯

M 1 M 2 z 1 z 2 z z 2

z z, iz, i

A + iB

z = a + ib z1

1

z+1

z z1 π 2

z+1

z z, z 2 , z 3 z

z C z, z (1 z)

C

1

|z 1| 1, |z + 1| 1.

−−→ O (O, u , v )

(A 0 , A 1 , A 2 , A 3 , A 4 )

u

= OA

0

C

ω 0 ,

,

ω 4 A 0 ,

{0, 1, 2, 3, 4} 1 + ω 1 + ω

2

1

+ ω

3

1

+

,

A 4 ω k

ω 4 = 0

1

= ω 1 k

k

cos( 2π ) 4z 2 + 2z 1 = 0 cos( 2π )

5

5

B 1 BA 2 sin 10

5 sin 10 = cos 2π

2 1

J C [BI) BI BJ

I

π

π

5

2 i C I

θ R

e iθ = cos θ + i sin θ.

θ R

cos θ =

e + e

2

sin θ =

e e

2i

.

a, b R

2 cos a cos b

;

2 sin a sin b

;

cos 2 a

;

sin 2 a.

e ix e iy = e i(x+y) x, y R sin(x + y) cos(x + y) tan(x + y) x y sin(2x) cos(2x) tan(2x) x, y R

θ R

cos x sin x tan x x = π + 2kπ , k Z

2

(cos θ + i sin θ) n = cos() + i sin().

cos(3x) sin(3x) sin x cos x

cos 5θ cos 8θ sin 6θ sin 9θ

θ sin 3 θ sin 4 θ cos 5 θ cos 6 θ θ

cos 5θ sin 5θ cos θ sin θ

sin θ

θ R cos θ

cos(2θ) sin(2θ) cos(3θ) sin(3θ) cos( π )

3

1 + cos 2 x cos 3 x + 2 sin 2 x

 (cos 5x)(sin 3x) sin x cos x x C = 1+cos x+cos .+cos nx = k=0 n cos kx

S = sin x + sin 2x +

R

+ sin nx = k=0 n sin kx C S

1 1

sin x =

2 ,

cos x = 2 ,

tan x = 1,

R

cos(5x) = cos 2π

3

x .

 sin(25π/3), cos(19π/4), tan(37π/6). 2 > 0 2 sin 2 x−3 sin x−2 = 0 2 sin 2 x−3 sin x−

f (x) = cos 3x + cos 5x.

R ]π, π]

x [π, π] 1 + cos x + | sin x/2|

sin (5x) = sin 2π + x

3

sin 2x π = cos x

3

3

cos (3x) = sin (x)

m 3 cos(x) + sin(x) = m

m = 2

R

cos(5x) + cos(3x) cos(x) 2 cos 2 (x) 9 cos(x) + 4 > 0.

R

 cos 2 (x) − sin 2 (x) = sin(3x) <